A systematic review of the early dialogue frameworks used within health technology assessment and their actual adoption from HTA agencies - Nora Ibargoyen-Roteta; Lorea Galnares-Cordero; Gaizka Benguria-Arrate; Kelly Rocío Chacón-Acevedo; María Paula Gutiérrez-Sepulveda; Eduardo Low-Padilla; Ilich Herbert De La Hoz-Siegler; Claudia Isabel Guevara-Pérez; Ángel del Pozo-Pérez; Marta Suárez; Hans Peter Dauben; Maximilian Otte; et al. (Frontiers Media S.A., 2022)
IntroductionEarly advice in the process of developing health technologies allows manufacturers to plan their production and transfer to health care systems more accurately. This review aims to describe frameworks used within HTA and their current use by HTA Agencies.Material and methodsWe carried out a systematic literature review in Pubmed, Embase, Scopus, and WoS, including all references published in Spanish and English. This was last updated in March 2022. We extracted all available information regarding the organizations involved, services offered, types of technology, collaborators involved, fees, output and impact. Websites of several HTA organizations and Google were also searched in order to update and complete the information obtained from this generic search.ResultsFive-hundred and forty one articles were identified and screened, of which 26 met the eligibility criteria and were selected. Seven of them were non-systematic reviews that described two or more HTA organizations. Ten studies were focused on the advice offered by individual organizations, and eight described the EMA and EUnetHTA parallel or joint advice. We found variations in the technology assessed, services offered, stage of development and costs for advisory services.ConclusionsEarly and scientific advice would help manufacturers focus their product development on what is needed for the management of specific diseases. Most of the examples or services found refer to drugs as well as to some medical devices and diagnostics. A common definition of the type of advice that could be offered for different health technologies by HTA bodies to ascertain health care systems and manufacturers' needs, in addition to the timeline in which that advice needs to be given, would help HTA bodies provide the right support at the right time.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020219401, PROSPERO CRD42020219401.